Analysis of Advertising Ethics Violations in Television Advertisements: Reject the Wind Version by Rhenald Kasali and Andy F Noya - Fakhrudin, Ammar; Azhar Syuhada, Muhammad; Desti Nur Rahmadina, Andini (Educationist: Journal of Educational and Cultural Studies, 2023)
At this time there are a lot of herbal medicine company products that offer various product variants that make competition in the market very tight, it is a natural thing in this era, they make new innovations in order to maintain their company so that they can still compete in the current era and still exist in the world. market. Then in terms of marketing these products must also compete to survive in the current period. One of the market leaders in the herbal medicine company now is PT. Sidomuncul, in this case, the herbal medicine product managed by Sidomuncul, is one of customer loyalty. In marketing PT. Sidomuncul made an advertisement in the form of a video broadcast on television with a duration of 30 seconds, but the advertisement was deemed to have violated the Indonesian broadcasting code of ethics. But apart from the broadcasting code of ethics, there are also advertising ethics that every advertiser must obey. In this study, the researchers discussed the application of ethical advertising principles to the Rhenald Kasali and Andy F Noya version of Tolak Angin advertisements. The purpose of this study was to analyze and explore the Rhenald Kasali and Andy F Noya version of Tolak Angin advertisements. The method used by the researcher is qualitative by using content analysis and validation of the data that has been observed, then the researcher looks for some references that support this research.